1999
DOI: 10.1038/sj.bjc.6690283
|View full text |Cite
|
Sign up to set email alerts
|

The IgG1/G2 subclass shift – a sensitive, tissue non-specific marker for malignancy. Diagnostic performance with squamous cell carcinoma of the head and neck

Abstract: Summary A significant decrease in %IgG1 accompanied by an increase in %IgG2 in total serum IgG has been previously reported as a highly sensitive marker for detecting early stages of carcinomas of various localizations. Here we investigated the question as to whether this phenomenon is also observed in sera of patients with squamous cell carcinoma of the head-neck region (SCC-HN), and to evaluate its diagnostic performance in the post-operative monitoring. Using quantitative affinity chromatography, serum conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…Possible explanations for this shift are that CagA could preferentially evoke T-helper 1 (Th1) responses, as has been observed in peptic ulcer patients (D'Elios et al, 1997), or that the IgG2 antibody response increases with age (Lottenbach et al, 1999). Alternatively, the shift might be related to the carcinogenesis process C. F. de la Cruz-Herrera and others itself, as patients with cancer usually show a characteristic and significant alteration in the pattern of serum IgG subclasses, with an increase in IgG2 and a reduction in IgG1 (Schauenstein et al, 1997;Anderhuber et al, 1999). Analogous results have been observed in rodent models (Haddada et al, 1984;Weblacher et al, 1993).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Possible explanations for this shift are that CagA could preferentially evoke T-helper 1 (Th1) responses, as has been observed in peptic ulcer patients (D'Elios et al, 1997), or that the IgG2 antibody response increases with age (Lottenbach et al, 1999). Alternatively, the shift might be related to the carcinogenesis process C. F. de la Cruz-Herrera and others itself, as patients with cancer usually show a characteristic and significant alteration in the pattern of serum IgG subclasses, with an increase in IgG2 and a reduction in IgG1 (Schauenstein et al, 1997;Anderhuber et al, 1999). Analogous results have been observed in rodent models (Haddada et al, 1984;Weblacher et al, 1993).…”
Section: Discussionsupporting
confidence: 59%
“…To date, there are only two reports on the IgG subclass response to CagA in children and young adults with benign diseases; CagA is predominantly recognized by IgG1, followed by IgG3 and then IgG2, and it fails to stimulate an IgG4 response (Dzierzanowska-Fangrat et al, 2003;Du et al, 2006). As in many infections, the IgG subclass response to infecting pathogens has been associated with the severity of clinical symptoms, and because patients with malignant diseases exhibit a significant alteration in the composition of serum IgG subclasses (Hussain et al, 1995;Lagacé et al, 1995;Schauenstein et al, 1997;Anderhuber et al, 1999), the present work aimed to evaluate the total IgG antibody response and that of the subclasses IgG1 and IgG2 against H. pylori antigens in patients with GC, intestinal metaplasia (IM) or NAG.…”
Section: Introductionmentioning
confidence: 99%
“…1 This phenomenon has been observed in patients with carcinomas of the mammary gland, 2,3 the female reproductive tract, 4 and the colorectal region, 5 and very recently with squamous cell carcinomas of the head and neck region. 6 Organmatched benign diseases and other nonmalignant diseases investigated so far have not shown comparable changes in the IgG subclass pattern. With certain tumor locations, this IgG subclass shift was found to exhibit diagnostic sensitivities and specificities that were comparable or, especially at early tumor stages, by far superior to conventional serologic tumor markers.…”
Section: Results Absolute Levels Of Igg Subclass Messenger Ribonuclementioning
confidence: 88%
“…6 The aim of the current study was to investigate the mechanism(s) responsible for the tumor-associated shift in IgG subclass serum levels. In particular, the question was addressed as to whether this phenomenon was detectable at the level of the IgG-producing B lymphocytes.…”
Section: Results Absolute Levels Of Igg Subclass Messenger Ribonuclementioning
confidence: 99%
“…It has also been suggested that the malignant process itself could interfere with the biosynthesis of IgG subclasses at the B-lymphocyte level. 22 An IgG1/G2 subclass shift has been reported in subjects with squamous cell carcinoma of the head and neck, breast cancer, colorectal cancer and with carcinomas of various locations of the female reproductive tract. [22][23][24] This effect of malignant tumors may be mediated by modulation of the secretion of certain cytokines and/or their soluble receptors.…”
Section: Discussionmentioning
confidence: 99%